CORPORATE SOCIAL RESPONSIBILITY AND CREATING SHARED VALUE: A PRELIMINARY STUDY FROM INDONESIA - Suripto Suripto (International Journal of Contemporary Accounting, 2019)
As a country who has a mandate for energy and extractive companies to implement and disclose Corporate Social Responsibility (CSR) program, Indonesia emphasizes the importance of CSR and Creating Shared Value (CSV) practices. As CSV is a new concept, which is considered as more comprehensive compared to CSR, this paper aims to provide a preliminary picture of how stakeholders understand and differentiate their perceptions on both CSR and CSV concepts. This study examines the different stakeholders’ perceptions of CSR and CSV concepts. This study targeted 50 samples of stakeholders from companies that have created shared values and disclosed them through their Sustainability Report, Annual Report, as well as website. Paired Sample Test, Independent Sample T-Test, and ANOVA test were carried out as the analytical method. The results show that there are different perceptions among stakeholders on CSR and CSV concepts in Indonesia. Different stakeholder types, internal and external, also contributes to a different perception of CSR and CSV. Likewise, the diversity of stakeholder positions, from Director; Manager; Corporate Secretary; Employee; Supplier; and Sub-District Head (Camat and Lurah), affects their different perceptions of CSR and CSV. On the contrary, different types of gender among stakeholders do not result in any significant difference in their perceptions of CSR and CSV concepts. This pilot study developed a questionnaire which adopts a theory which highlights the difference between CSR and CSV concepts. Previously, there is no research regarding stakeholders which emphasizes the different concept of CSR and CSV in Indonesia nor other countries. This study will fill some of that gap which then will lead to conducting a major study in the same field.